Spanish Philosophy of Technology Contemporary Work from the Spanish Speaking Community (Philosophy of Engineering and Technology,, 2018)
This volume features essays that detail the distinctive ways authors and researchers in Spanish speaking countries express their thoughts on contemporary philosophy of technology. Written in English but fully capturing a Spanish perspective, the essays bring the views and ideas of pioneer authors and many new ones to an international readership. Coverage explores key topics in the philosophy of technology, the ontological and epistemological aspects of technology, development and innovation, and new technological frontiers like nanotechnology and cloud computing. In addition, the book features case studies on philosophical queries. Readers will discover such voices as Miguel Ángel Quintanilla and Javier Echeverría, who are main references in the current landscape of philosophy of technology both in Spain and Spanish speaking countries; José Luis Luján, who is a leading Spanish author in research about technological risk; and Emilio Muñoz, former head of the Spanish National Research Council and an authority on Spanish science policy. The volume also covers thinkers in American Spanish speaking countries, such as León Olivé, an influential researcher in ethical issues; Judith Sutz, who has a very recognized work on social issues concerning innovation; Carlos Osorio, who focuses his work on technological determinism and the social appropriation of technology; and Diego Lawler, an important researcher in the ontological aspects of technology.